From Regulation to Realization: Legal Analysis of Electric Vehicle Policy in Indonesia, India, and Thailand - Widhiyanti, Hanif Nur; Prabowo, Ipop Abdi; Mohd. Hussein, Safinaz (Universitas Negeri Semarang, 2025)
National electric cars play a strategic role in achieving the Sustainable Development Goals. Challenges in developing nationally electric-based cars include infrastructure, regulations, and the readiness of the domestic industry to adopt new technologies. This article examines the challenges and opportunities within Indonesian law to develop a national electric car industry. This article is a legal study with a comparative approach focusing on India, Thailand, and Malaysia to identify best practices in their national electric car policy frameworks. The study reveals that Presidential Regulation No. 79 of 2023 on Electric Motor Vehicles is a stage to support sustainable development and a commitment to international environmental law such as the Paris Agreement. Although the Domestic Component Level policy has faced criticism in the context of global trade, this approach can be justified under international law if it aims at environmental protection, is proportionate, and is not discriminatory. This aligns with the WTO jurisprudence in the 2012 China-Raw Materials case and the recognition that Article XX of GATT allows countries to implement environmentally friendly policies. Thus, domestic component level protection is not protectionism but a part of a